Impact of high-dose folic acid supplementation in pregnancy on biomarkers of folate status and 1-carbon metabolism: An ancillary study of the Folic Acid Clinical Trial (FACT). Issue 5 (1st March 2021) - Murphy, Malia S Q; Muldoon, Katherine A; Sheyholislami, Hauna; Behan, Nathalie; Lamers, Yvonne; Rybak, Natalie; White, Ruth Rennicks; Harvey, Alysha L J; Gaudet, Laura M; Smith, Graeme N; Walker, Mark C; Wen, Shi Wu; et al.
ABSTRACT: Background: Periconceptional folic acid (FA) supplementation is recommended to prevent the occurrence of neural tube defects. Currently, most over-the-counter FA supplements in Canada and the United States contain 1 mg FA and some women are prescribed 5 mg FA/d. High-dose FA is hypothesized to impair 1-carbon metabolism. We aimed to determine folate and 1-carbon metabolism biomarkers in pregnant women exposed to 1 mg or 5 mg FA. Objectives: This was an ancillary study within the Folic Acid Clinical Trial (FACT), a randomized, double-blinded, placebo-controlled, phase III trial designed to assess the efficacy of high-dose FA to prevent preeclampsia. Methods: For FACT, women were randomized at 8–16 gestational weeks to receive daily 4.0 mg FA (high dose) or placebo (low dose) plus their usual supplementation (≤1.1 mg). Women were recruited from 3 Canadian FACT centers and provided nonfasting blood samples at 24–26 gestational weeks for measurement of RBC and serum total folate, serum unmetabolized FA (UMFA), tetrahydrofolate (THF), 5-methylTHF, 5-formylTHF, 5, 10-methenylTHF, and MeFox (pyrazino-s-triazine derivative of 4α-hydroxy-5-methylTHF, a 5-methylTHF oxidation product); total vitamins B-12 and B-6; and plasma total homocysteine. Group differences were determined using χ 2, Fisher exact, and Wilcoxon rank-sum tests. Results: Nineteen (38%) women received high-dose FA and 31 (62%) received low-dose FA. The median RBC folate concentration was 2701 (IQR: 2243–3032) nmol/L and did not differ between groups. The high-dose group had higher serum total folate (median: 148.4 nmol/L, IQR: 110.4–181.2; P = 0.007), UMFA (median: 4.6 nmol/L, IQR: 2.5–33.8; P = 0.008), and 5-methylTHF (median: 126.6 nmol/L, IQR: 98.8–158.6; P = 0.03) compared with the low-dose group (median: 122.8 nmol/L, IQR: 99.5–136.0; median: 1.9 nmol/L, IQR: 0.9–4.1; median: 108.6 nmol/L, IQR: 96.4–123.2, respectively). Other biomarkers of 1-carbon metabolism did not differ. Conclusions: High-dose FA supplementation in early pregnancy increases maternal serum folate but not RBC folate concentrations, suggesting tissue saturation. Higher UMFA concentrations in women receiving high-dose FA supplements suggest that these doses are supraphysiologic but with no evidence of altered 1-carbon metabolism.